Microscopical Investigation of Sideritis taurica - Fatima Kazbekovna Serebryanaya; Irina Konovalova (Borneo Journal of Pharmacy, 2020)
This research presents the results of the morphological-anatomical study of grass organs above ground (leaves, stems, and flowers) from Sideritis taurica Steph. ex Willd. from the Lamiaceae family. The range of distribution of this species covers Eastern Europe, including Crimea, Caucasus. This plant is commonly found as an ornamental plant and grows in the southern and central regions of Russia. The purpose of this study is the anatomical and morphological study of the vegetative organs of S. taurica and the formation of diagnostic signs for reliable plant identification. The research material used was S. taurica herbicide samples collected in Crimea on the slopes of Mount Ay-Petri. Plant material is fixed in the glycerin : water system in a ratio of 1 : 1. Cross-section of stems and leaves is carried out using blades. The study was conducted with the morphological-anatomical method. The results obtained indicate the anatomical structure of the lamina, stem, and flower of the plant that has been studied. Anomocytic types of stomatal devices, unicellular and multicellular trichomes, located on the upper and lower sides of the leaf, as well as on the corolla stem and epidermis, have been discovered. The study carried out is part of the S. taurica complex pharmacognostic study.